Retrospective Evaluation of Horses Diagnosed with Neuroborreliosis on Postmortem Examination: 16 Cases (2004–2015). (21st June 2016) - Johnstone, L.K.; Engiles, J.B.; Aceto, H.; Buechner‐Maxwell, V.; Divers, T.; Gardner, R.; Levine, R.; Scherrer, N.; Tewari, D.; Tomlinson, J.; Johnson, A.L.
Abstract : Background: Equine neuroborreliosis (NB), Lyme disease, is difficult to diagnose and has limited description in the literature. Objective: Provide a detailed description of clinical signs, diagnostic, and pathologic findings of horses with NB. Animals: Sixteen horses with histologically confirmed NB. Methods: Retrospective review of medical records at the University of Pennsylvania and via an ACVIM listserv query with inclusion criteria requiring possible exposure to Borrelia burgdorferi and histologic findings consistent with previous reports of NB without evidence of other disease. Results: Sixteen horses were identified, 12 of which had additional evidence of NB. Clinical signs were variable including muscle atrophy or weight loss (12), cranial nerve deficits (11), ataxia (10), changes in behavior (9), dysphagia (7), fasciculations (6), neck stiffness (6), episodic respiratory distress (5), uveitis (5), fever (2), joint effusion (2), and cardiac arrhythmias (1). Serologic analysis was positive for B. burgdorferi infection in 6/13 cases tested. CSF abnormalities were present in 8/13 cases tested, including xanthochromia (4/13), increased total protein (5/13; median: 91 mg/dL, range: 25–219 mg/dL), and a neutrophilic (6/13) or lymphocytic (2/13) pleocytosis (median: 25 nucleated cells/μL, range: 0–922 nucleated cells/μL). PCR on CSF for B. burgdorferi was negative in the 7 cases that were tested. Conclusion and Clinical Importance: Diagnosis of equine NB is challenging due to variable clinical presentation and lack of sensitive and specific diagnostic tests. Negative serology and normal CSF analysis do not exclude the diagnosis of NB.